Human capital and organizational performance: Moderating effects of dynamism, uncertainly and munificence - Adnan, Zurina; Abdullah, Hazman Shah; Ahmad, Jasmine (2008)
Heterogeneous performance of the firms is explained by several different theories. Following the notion of resource-based view, this conceptual study attempts to bring in the human capital theory to explain firm performance. Empirical researches studying human capital management are numerous in western countries. However, not much can be said about the deployment of Malaysian human capital especially in R&D firms since very little empirical studies have been done to understand this sector. Therefore, in general this paper intends to argue the role of human capital in influencing performance. In specific, it attempts to examine the relationship between human capital and organizational performance and whether environmental dynamism, uncertainty and munificence have moderating effects on this relationship.